Perinatal palliative care in sub-Saharan Africa: recommendations for practice, future research, and guideline development - Abayneh, Mahlet; Rent, Sharla; Ubuane, Peter Odion; Carter, Brian S.; Deribessa, Solomie Jebessa; Kassa, Betelehem B.; Tekleab, Atnafu Mekonnen; Kukora, Stephanie K. (Frontiers in Pediatrics, 2023)
Worldwide, sub-Saharan Africa has the highest burden of global neonatal mortality (43%) and neonatal mortality rate (NMR): 27 deaths per 1000 live births. The WHO recognizes PC as an integral, yet underutilized, component of perinatal care for pregnancies at risk of stillbirth or early neonatal death, and for neonates with severe prematurity, birth trauma or congenital anomalies. Despite bearing a disproportionate burden of neonatal mortality, many strategies to care for dying newborns and support their families employed in high-income countries (HICs) are not available in low-and-middle-income countries (LMICs). Many institutions and professional societies in LMICs lack guidelines or recommendations to standardize care, and existing guidelines may have limited adherence due to lack of space, equipment, supplies, trained professionals, and high patient load. In this narrative review, we compare perinatal/neonatal PC in HICs and LMICs in sub-Saharan Africa to identify key areas for future, research-informed, interventions that might be tailored to the local sociocultural contexts and propose actionable recommendations for these resource-deprived environments that may support clinical care and inform future professional guideline development.